Harmonization Of State Law And Customary Law In Traditional Health Service Practices In Indonesia - Teguh Adi Partama; Ida Bagus Tatwa Yatindra; I Putu Hari Jaya Tirta; Marsudi Dedi Putra (Dinasti Research, 2026)
This study aims to analyze the harmonization between state law and customary law in traditional health service practices in Indonesia, identify the forms of incompatibility that occur, and formulate efforts to create harmony between the two legal systems through normative juridical research methods that focus on the study of legal norms, laws and regulations, and doctrines. The data collection technique is carried out through a literature study of primary, secondary, and tertiary legal materials which are then analyzed qualitatively to produce logical and structured legal arguments. The current arrangement of traditional health services has been transformed from Law Number 36 of 2009 to Law Number 17 of 2023 concerning Health which places the practice as an integral part of the national health system. Customary law acts as a living law that provides social legitimacy, regulates practitioner ethics through communal values, and maintains the authenticity of traditional knowledge that has been passed down from generation to generation. Efforts to harmonize are carried out through constitutional recognition of customary law communities and the integration of local norms into formal regulations to ensure security and service standards for communities without erasing cultural identity. This synergy creates dual protection for Indonesia's ethnobotanical wealth from exploitation by outsiders while ensuring that every health practice can be legally and empirically accounted for. Such alignment requires ongoing dialogue between governments, indigenous leaders, and health practitioners to address the challenges of the differences between modern medical methodologies and traditional healing techniques.